Traditional Chinese medicines and natural products targeting immune cells in the treatment of metabolic-related fatty liver disease - Li, Zhen; Ouyang, Hao; Zhu, Junfeng (Frontiers in Pharmacology, 2023)
MAFLD stands for metabolic-related fatty liver disease, which is a prevalent liver disease affecting one-third of adults worldwide, and is strongly associated with obesity, hyperlipidemia, and type 2 diabetes. It encompasses a broad spectrum of conditions ranging from simple liver fat accumulation to advanced stages like chronic inflammation, tissue damage, fibrosis, cirrhosis, and even hepatocellular carcinoma. With limited approved drugs for MAFLD, identifying promising drug targets and developing effective treatment strategies is essential. The liver plays a critical role in regulating human immunity, and enriching innate and adaptive immune cells in the liver can significantly improve the pathological state of MAFLD. In the modern era of drug discovery, there is increasing evidence that traditional Chinese medicine prescriptions, natural products and herb components can effectively treat MAFLD. Our study aims to review the current evidence supporting the potential benefits of such treatments, specifically targeting immune cells that are responsible for the pathogenesis of MAFLD. By providing new insights into the development of traditional drugs for the treatment of MAFLD, our findings may pave the way for more effective and targeted therapeutic approaches.